Mixed integer non-linear programming and Artificial Neural Network based approach to ancillary services dispatch in competitive electricity markets - Canizes, Bruno; Soares, João; Faria, Pedro; Vale, Zita (Applied energy, 2013)
•Ancillary services market management.•Ancillary services requirements forecast based on Artificial Neural Network.•Ancillary services clearing mechanisms without complex bids and with complex bids. Ancillary services represent a good business opportunity that must be considered by market players. This paper presents a new methodology for ancillary services market dispatch. The method considers the bids submitted to the market and includes a market clearing mechanism based on deterministic optimization. An Artificial Neural Network is used for day-ahead prediction of Regulation Down, regulation-up, Spin Reserve and Non-Spin Reserve requirements. Two test cases based on California Independent System Operator data concerning dispatch of Regulation Down, Regulation Up, Spin Reserve and Non-Spin Reserve services are included in this paper to illustrate the application of the proposed method: (1) dispatch considering simple bids; (2) dispatch considering complex bids.